Laboratory Profiles and Imaging Findings of Abdominal Tuberculosis Patients: Experience of 100 Cases in Bangladesh - Kudrat E Khuda, Iftekhar Md; Momotaj, Mst Tanjila; Hakim, Sheikh Mohd A; Alom, Md Ashraful; Ahmed, Sk Shamim; Kundu, Sampa Rani; Alam, Md Mahbubul (Bangladesh Journal of Medical Microbiology, 2023)
Background: Variations of laboratory profiles and imaging findings may occur among the abdominal tuberculosis patients. Objectives: The purpose of the present study was to laboratory profiles and imaging findings of abdominal tuberculosis patients. Methodology: This descriptive cross sectional study was conducted in the Department of Surgery of Rajshahi Medical College Hospital, Rajshahi, Bangladesh from January 2014 to December 2015 for two years. This study included patients who were admitted in surgery units of Rajshahi Medical College Hospital, Rajshahi, Bangladesh who were diagnosed as abdominal tuberculosis with or without associated pulmonary or nodal tuberculosis. Different laboratory tests were performed and were recorded. The imaging techniques like barium meal and Ultrasonography of the abdomen were also performed during diagnosis of the patient. Results: A total number of 100 cases were included in the study. The most common age group was 20 to 30 Years of age group which was 52.0% cases. In this study 18 cases were positive histological examination of intestine for tuberculosis. About 12 cases were node-positive, 6 cases were ADA positive, 20 patients underwent positive colonoscopy, 26 cases were FNAC positive in caecal growth and lymphadenopathy, 12 cases ware positive radiological findings, 3 cases were positive histopathology in which tissue taken by laparoscopy and remaining 3 was confirmed by isolation of organism by smear and culture for AFB of ascetic fluid. In plain X-Ray of abdomen, 48 patients had features of intestinal obstruction, 7 patients had pneumoperitoneam, 4 patients had ground glass opacity with pneumoperitoneam and only 1 patient had calcified lymph node and remaining 40 patients had normal radiological findings. Conclusion: In conclusion most of the abdominal tuberculosis patients are positive in histopathological examination and X-ray of abdomen. Bangladesh Journal of Medical Microbiology, July 2022;16(2):47-52